Current Recommendations for Airway Management Techniques in COVID-19 Patients without Respiratory Failure Undergoing General Anaesthesia: A Nonsystematic Literature Review - Grigonytė, Milda; Kraujelytė, Agnė; Januškevičiūtė, Elija; Šėmys, Giedrius; Bružytė-Narkienė, Greta; Kriukelytė, Oresta; Kontrimavičiūtė, Eglė; Valevičienė, Nomeda Rima (Acta medica Lituanica, 2021)
Background. Since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) first emerged, many articles have been published on airway management for coronavirus disease 2019 (COVID-19) patients. However, there is a lack of clear and concise conceptual framework for working with infected patients without respiratory failure undergoing general anaesthesia compared to noninfected patients. The aim of this article is to review current literature data on new challenges for anaesthesia providers, compare standard airway management techniques protocols with new data, and discuss optimisation potential. Materials and methods. Literature search was performed in Google Scholar and PubMed databases using these keywords and their combinations: anaesthesia, preoxygenation, airway management, difficult airway, SARS-CoV-2, COVID-19. The following nonsystematic review is based on a comprehensive literature search of available data, wherein 41 articles were chosen for detailed analysis. Summarised and analysed data are presented in the article. Results. SARS-CoV-2 has unique implications for airway management techniques in patients without respiratory failure undergoing general anesthesia. Main differences with the standard practice include: institutional preparedness, team composition principles, necessary skills, equipment, drugs, intubation and extubation strategies. Failed or difficult intubation is managed with predominance of emergency front of neck access (FONA) due to increased aerosol generation. Conclusions. Airway management techniques in COVID-19 patients without respiratory failure are more challenging than in noninfected patients undergoing general anaesthesia. Safe, accurate and swift actions avoid unnecessary time delay ensuring the best care for patients, and reduce risk of contamination for staff. Appropriate airway strategy, communication, minimisation of time for aerosol generating procedures and ramped-up position aid to achieve these goals. During the pandemic, updated available literature data may change clinical practice as new evidence emerges.